(untitled) - Grey, Tim (Indianapolis, Ind., 2007)
Get the most out of Lightroom with Tim Grey as your guide by reducing the time and effort you spend storing, selecting, and editing your digital images. Adobe’s new Lightroom software, together with this practical guide, explains everything from importing and cataloguing to processing and archiving. Whether you’re a professional photographer or advanced amateur, you’ll find ways to work efficiently with Lightroom in order to improve your productivity and get the results you want.
Keywords: Adobe Photoshop lightroom,Photography; Digital techniques; Computer programs